Facile preparation of sphere-like copper ferrite nanostructures and their enhanced visible-light-induced photocatalytic conversion of benzene - Shen, Y.; Wu, Y.; Xu, H.; Fu, J.; Li, Xin Yong; Zhao, Q.; Hou, Y. (2013)
Spinel copper ferrite nanospheres with diameters of about 116 nm were synthesized in high yield via a facile solvothermal route. The prepared nanospheres had cubic spinel structure and exhibited good size uniformity and regularity. The band-gap energy of CuFe2O4 nanospheres was calculated to be about 1.69 eV, indicating their potential visible-light- induced photocatalytic activity. The dramatically enhanced photocatalytic activity of the CuFe2O4 nanospheres was evaluated via the photocatalytic conversion of benzene under Xe lamp irradiation. By using the in situ FTIR technique, ethyl acetate, carboxylic acid and aldehyde could be regarded as the intermediate products, and CO2 was produced as the final product during the reaction process. This study provided new insight into the design and preparation of functional nanomaterials with sphere structure in high yield, and the as-grown architectures demonstrated an excellent ability to remove organic pollutants in the atmosphere.